Development Of Interactive Learning Media Using Teachmint To Improve Arabic Speaking Proficiency - Sakka, Abdullah; N. Hula, Ibnu Rawandhy; Una, Hirsan; Saleh, Sriwahyuningsih; Doni, Chaterina Putri; Godat Arrashe, Yousif Abdelmannan Mohamed (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This research aims to develop online-based interactive learning media using the teachmint application to improve students' Arabic speaking proficiency. The research uses the Research and Development method with the ADDIE model (analysis, design, development, implementation, and evaluation). The population of this study is 42 students of Ma'had al-Husain bin Ali UMG, Indonesia. Data collection was obtained through observation, interviews, questionnaires, and tests. The study results show that (1) Needs analysis identifies the need for technology-based interactive learning media to improve speaking proficiency and the need for more development of special media for this proficiency. (2) Media design produces ta'bir material with four marhalah/levels. The complete material starts from the initial menu display to the evaluation. (3) The development results have been validated by 85.71% of media experts, 89.29% of material experts, and 92.86% of linguists with worthy predicates. (4) The implementation results showed that the learning media was feasible and exciting to increase students' mastery of speaking proficiency with a response score of 83.93%. (5) The evaluation results showed an increase in the average score of pre-tests 76.09 and post-test 84.6 with paired samples t-test significance of 0.000 < 0.05. The research contributes to improving the quality of students' learning of Arabic speaking proficiency by developing online-based interactive media.